EFFECT OF UMMB SUPPLEMENTARY FEEDING ON BLOOD BIOCHEMICAL PROFILES IN DAIRY CATTLE - RANDHAWA, B; PANGAONKAR, G R; BRAR, P S; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2023)
Extent and duration of negative energy balance in recently calved dairy animals is determinant of their postpartum reproductive efficiency. Urea molasses multi-nutrient block (UMMB) supplementation in early postpartum period hastens onset of postpartum ovarian activity. The present study focuses on the certain biochemical changes following UMMB supplementation in recently calved dairy buffaloes. Blood glucose concentrations were significantly higher in the supplemented than the un-supplemented buffaloes. Blood glucose concentrations were significantly higher in the cycling buffaloes than the an estrus buffaloes. A significant positive correlation was found between blood glucose and plasma insulin concentrations. The overall average plasma insulin concentrations were significantly higher and of free fatty acids significantly lower in the supplemented than the un•supplemented controls. Overall biochemical changes revealed negative energy balance to be of lower extent and less duration in UMMB supplemented buffaloes, which might have favored the early onset of ovarian activity in supplemented early postpartum buffaloes.